Socio-economic Conflicting Issues Embedded in Bangladesh Liberation War in 1971: Coverage of the New York Times - Abedin, Zainul (Journal of Applied Business and Economics, 2019)
This study explored the impacts of the coverage of the Liberation War of Bangladesh in 1971 by the New York Times. In the backdrop of the Cold War phenomena the United States reportedly took a position against Bangladesh’s liberation while the war created a humanitarian orgy of killings, rapes, and the dislocation of millions of people. The war impacts still haunt the nation as the incumbent Bangladesh government began trials of “war crimes” and already executed some opposition leaders for alleged collaboration with the Pakistani Army. As the first textual analysis of the Times’ coverage of the Bangladesh War in the postcolonial era, the study revealed that the Times played a humanitarian role but was seemed influenced by the confrontation with the Nixon Administration on secret papers and policies of wars, popularly known as “Pentagon Papers.”